Investigation of Ways of Dynamic Range Expansion for Broadband Receiver Microwave Devices in Multi-Signal Mode - S. A. Bogdanov; P. V. Kupriyanov; S. V. Nikolaev; S. A. Petrov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The article investigates ways to expand the dynamic range of broadband microwave receiving devices. The task is to lim-it the output signals while increasing the upper boundary of the dynamic range by the criterion of the thirdorder inter-modulation component suppression. The main relations  determining the dynamic range boundary conditions are pre-sented. Experimental studies of three variants of constructing the broadband microwave receiver output path in two-ton mode of operation are carried out for:– an output amplifier with a point of 1 dB of output power compression at the level corresponding to safe output power;– a powerful output amplifier with a passive diode limiter on the output;– a powerful output amplifier with an automatic attenuation adjustment circuit connected to its input.The measurement results of the magnitude of intermodulation distortions suppression and output power are presented as a function of the input signal level for various nonlinear elements. Based on the analysis of the measured characteristics, an optimal technical solution is found for constructing an output path. The dynamic range is extended by more than 20 dB. Suppression of intermodulation components of the third order exceeds 60 dB. Effective functioning of the broadband receiver in multisign mode is ensured.